2020
DOI: 10.21203/rs.2.15658/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Thickness profiles of the corneal epithelium along the steep and flat meridians of astigmatic corneas after orthokeratology

Abstract: Background: To investigate the changes in corneal epithelial thickness along the principle meridians of astigmatic corneas after six months of overnight spherical myopic orthokeratology (OK) lens wear.Methods: A prospective study. Fifty-seven subjects with up to 1.50 diopters (D) of corneal toricity wore spherical OK lenses for 6 months. Evaluations of OK lens fit, visual acuity, refractions and corneal toricity (CT) were performed. Fourier-domain optical coherence tomography (FD-OCT) was conducted to measure … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…There are several studies not detecting short-term significant changes in MPET or reporting a temporal initial thickening with a posterior regression to baseline values, 15,16 while other studies have reported a significant thickening in MPET. 2,3,14,17,18 These contradictory results could be explained due to the difference in lens design, given that the curvature radii are different for each geometry. The CRT design, which was fitted in this study, was also used by Kim et al, 3 who found a MPET thickening after 2 weeks of OK use and, therefore, their follow-up period was longer than ours.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several studies not detecting short-term significant changes in MPET or reporting a temporal initial thickening with a posterior regression to baseline values, 15,16 while other studies have reported a significant thickening in MPET. 2,3,14,17,18 These contradictory results could be explained due to the difference in lens design, given that the curvature radii are different for each geometry. The CRT design, which was fitted in this study, was also used by Kim et al, 3 who found a MPET thickening after 2 weeks of OK use and, therefore, their follow-up period was longer than ours.…”
Section: Discussionmentioning
confidence: 99%
“…1 This technique generates changes in corneal epithelial thickness profile, with a redistribution of the epithelial layer from the center to the midperiphery. [2][3][4] Specifically, several studies have demonstrated that there is a thinning of the central epithelium, whereas the midperipheral area of this layer thickens due to the effect of the hydrodynamic forces associated with the OK treatment. 4 These changes are reversible as the cornea returns to its original state when the lens is removed.…”
mentioning
confidence: 99%
“…Following publication of the original article [ 1 ], we were notified that the authors would like to remove affiliation 2 (Sydney Eye Hospital, Sydney, NSW, 2000, Australia) from the author Xingtao Zhou and Yishan Qian, and affiliation 1 (Department of Ophthalmology, Eye and ENT Hospital, Fudan University; Key Laboratory of Myopia of The State Health Ministry, 200031, 83 Fenyang Road, Shanghai, People’s Republic of China) from the author Rajeev Krishnan Naidu.…”
mentioning
confidence: 99%